Driver Application Design for Logistics Movement Efficiency for PT. Dunia Multi Servindo (DMS) - Richard, Richard; Budiyantara, Agus; Perdana, Novario Jaya (Jutisi : Jurnal Ilmiah Teknik Informatika dan Sistem Informasi, 2024)
PT. Dunia Multi Servindo (DMS) is a logistics company managing the transportation of goods using manual processes such as e-mail, phone calls, and Excel, which are inefficient. This mobile application is designed to streamline job acceptance for drivers, enabling them to accept or decline tasks with clear reasons and access real-time information about goods and locations. The application was developed using the Incremental Model method and programmed in Dart and Flutter, with data stored in an open-source database. Testing was conducted using BlackBox and User Acceptance Testing methods. The results show that the application improves operational efficiency through document digitization, vehicle maintenance reporting, and centralized task assignments. The transition from manual to digital processes accelerates workflows, reduces errors, and lowers operational costs while strengthening the companyâ€™s reputation. This digital transformation lays the foundation for PT. DMS's future growth in addressing industry challenges.Keyword: Logistics; Mobile application; Distribution; Real-time; FlutterÂ AbstrakPT. Dunia Multi Servindo (DMS) adalah perusahaan logistik yang mengelola pengiriman barang dengan proses manual melalui e-mail, telepon, dan Excel, yang kurang efisien. Aplikasi mobile ini dirancang untuk merampingkan proses penerimaan pekerjaan oleh pengemudi, memungkinkan mereka menerima atau menolak pekerjaan dengan alasan yang jelas, serta mengakses informasi barang dan lokasi secara real-time. Aplikasi dikembangkan menggunakan metode Incremental Model dan bahasa pemrograman Dart serta Flutter, dengan data disimpan dalam database open-source. Pengujian dilakukan menggunakan metode BlackBox dan User Acceptance Testing. Hasilnya, aplikasi meningkatkan efisiensi operasional melalui digitalisasi dokumen, pelaporan pemeliharaan kendaraan, dan penugasan pekerjaan secara terpusat. Transisi dari sistem manual menjadi digital ini mempercepat proses kerja, mengurangi kesalahan, dan menurunkan biaya operasional, sekaligus memperkuat reputasi perusahaan. Transformasi digital ini menjadi dasar pertumbuhan masa depan PT. DMS dalam menghadapi tantangan industri.Â